2021
DOI: 10.1007/s00431-021-04096-x
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-containing versus sodium-trace preparations of IVIG for children with Kawasaki disease in the acute phase

Abstract: Objectives: Kawasaki disease (KD) is an acute systemic vasculitis that most commonly causes acquired cardiac disease in children in developed countries. The most highly recommended treatment for KD is 2 g/kg intravenous immunoglobulin (IVIG). There are two types of IVIG, sodium-containing (high Na) and sodium-trace (low Na) preparations. However, few studies have compared the effects of these two preparations for superiority. The purpose of this study was to compare outcomes between high and low Na IVIG prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Although standard treatments are available for acute-phase KD, the efficacy of different brands or preparations of IVIG for KD has attracted attention. Suzuki et al (29) conducted a study of 42,345 KD children who received IVIG treatment. These authors found that 2.8% patients receiving high Na + concentration IVIG as initial treatment developed CAA compared to 3.2% of those who received low concentrations (p = 0.031).…”
Section: Discussionmentioning
confidence: 99%
“…Although standard treatments are available for acute-phase KD, the efficacy of different brands or preparations of IVIG for KD has attracted attention. Suzuki et al (29) conducted a study of 42,345 KD children who received IVIG treatment. These authors found that 2.8% patients receiving high Na + concentration IVIG as initial treatment developed CAA compared to 3.2% of those who received low concentrations (p = 0.031).…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] The consensus aims to provide a basis for the standardized clinical management of KD in China, ultimately achieving effective prevention of complications and sequelae in children with KD and reducing the risk of cardiovascular events and death in children with KD. 20,21…”
Section: Introductionmentioning
confidence: 99%